Learning Motivation among University Students in Tangerang Regency: A Descriptive Quantitative Study - Veronica Paula; Davoino Konyorah; Wanda G J Atafani; Yinti Werlina Boymau; Edson Kasenda (CV. Inara, 2026)
Background: Learning motivation plays a crucial role in students’ academic success, engagement, and persistence, particularly within higher education environments that demand high levels of cognitive, emotional, and behavioural involvement. Motivated students are more likely to actively participate in learning activities, apply effective learning strategies, and maintain resilience when facing academic challenges. Understanding students’ learning motivation is therefore essential for higher education institutions in designing supportive academic environments and evidence-based educational strategies.Objective: This study aimed to describe the level of learning motivation among university students in Tangerang Regency, Indonesia. Methods: A descriptive quantitative research design was employed in this study. A total of 395 university students were recruited using purposive sampling based on predefined inclusion criteria. Data were collected between January and April 2025 using a validated learning motivation questionnaire that measured intrinsic and extrinsic motivation dimensions. The questionnaire was distributed online via Google Forms to ensure accessibility and efficiency. Data were analysed using univariate statistical analysis and are presented in the form of frequencies, percentages, means, and standard deviations. Results: The findings showed that most students (52.41%) demonstrated a high level of learning motivation. The descriptive analysis further indicated relatively high mean scores for both intrinsic and extrinsic motivation, suggesting that students’ learning motivation was supported by both internal factors, such as personal interest and self-development, and external factors, including academic environment and institutional support. Conclusion: University students in Tangerang Regency generally exhibit high learning motivation. These findings highlight the importance of maintaining and strengthening supportive academic environments to sustain students’ motivation and enhance academic engagement in higher education.